Measuring Science Teachers’ Digital Teaching Competence in Rural Area, Keerom Regency of Papua - Nurbaya Nurbaya; Hanida Listiani; Suriyah Satar; Cartika Candra Ledoh (Postgraduate, University of Mataram, 2025)
The demand of ICT-based learning required teachers to adapt 21st century teaching skills. These skills are encompassed in Digital Teaching Competence (DTC) developed from DogCompEdu Framework. The aim of this paper is to measure the DTC of science teachers in Keerom Regency of Papua. This research is developed through a 22-items and completed by 23 science teachers, with quantitative study with a descriptive approach. There are six dimensions measured in this study (professional engagement, digital resources, teaching and learning, assessment, empowering learners, and facilitating learner’s digital competence. The main results of the study show the level of DTC stood at medium to high category. Teachers who are still relatively young have a higher average questionnaire score than the older teacher age group. For the female teachers, the scores are slightly higher than male teachers. Teaching experience did not determine the level of DTC, but instead the competence measured relevant to years of experience using ICT-based learning class.